2019
DOI: 10.4236/ojpathology.2019.92004
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation between Histochemical Patterns of Connective Tissue Fibers and AgNORs in Breast Lesions

Abstract: Background: The precise histopathologic diagnosis of a breast lesion is the first step towards the most appropriate inclusive patient's management. The aim of this study was to evaluate the correlation between histochemical patterns of connective tissue fibers and NORs in breast lesions. Methodology: Patients with breast cancer (n = 25) were ascertained as the case group, and those with benign breast lesions were ascertained as a control group (n = 25). Histochemical evaluations of elastic fibers, reticular fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The cells and connective tissue changes of the ducts and stroma were prominent in the benign and malignant tumours. Several authors have reported that benign and malignant tumours undergo significant changes in the connective tissues especially in the collagen fibres morphology (Elasbali, 2019;Acerbi et al, 2015;Runa et al, 2017). These changes involve mostly increase deposition, thickening and reorganization of collagen fibres within the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The cells and connective tissue changes of the ducts and stroma were prominent in the benign and malignant tumours. Several authors have reported that benign and malignant tumours undergo significant changes in the connective tissues especially in the collagen fibres morphology (Elasbali, 2019;Acerbi et al, 2015;Runa et al, 2017). These changes involve mostly increase deposition, thickening and reorganization of collagen fibres within the matrix.…”
Section: Discussionmentioning
confidence: 99%